Symposium 2: Applying Universal Design for Learning guidelines to a blended learning course for prospective teachers - Mangiatordi, Andrea (Proceedings of the International Conference on Networked Learning, 2018)
Universal Design has been studied and applied in Education for some decades now, yet it seems still far from becoming a standard in instructional design practices. Teaching educators and prospective teachers how to make a curriculum accessible to students with different needs seems to be a priority for making instruction more and more accessible and inclusive is relevant in a Networked Learning perspective. The redesign of a blended learning course about Educational Technology to incorporate Universal Design principles is presented here. The participants, who were prospective teachers attending the fourth of a five-year graduate programme, were taught how to introduce Educational Technology in their lesson plans according to some basic principles of Universal Design, while the same principles were actually being used with them. Pre- and post-course survey data show an increase in various aspects, but mainly in the perceived self-efficacy in using Educational Technology, and in performance outcome expectations. The vast majority of participants also stated that the difficulty level of the course was not too distant from their confidence level. Some considerations are finally exposed, about the design challenges that are involved in universally designing a blended learning course.